Systematic Review with Network Meta-Analysis: Comparative Efficacy and Safety of Combination Therapy with Angiotensin II Receptor Blockers and Amlodipine in Asian Hypertensive Patients - Dae Wook Lee; Mira Jung; Hye Won Wang; Zainah Khan; Philippe Pinton (International Journal of Hypertension)
Background. Hypertension (HTN) is the leading risk factor for cardiovascular mortality globally. The WHO estimates a 60% increase in Asian HTN patients between 2000 and 2025. Numerous studies have compared safety and efficacy between antihypertensive classes, but in-class comparisons of angiotensin II receptor blockers (ARBs) in combination therapy (CT) (fixed-dose combination or dual combination) with a calcium channel blocker (CCB) are lacking in Asia. Objective. To compare the efficacy and safety of the various ARB-amlodipine CTs and amlodipine (AML) monotherapy for treatment of HTN in Asian population. Methods. A systematic literature review sourced Asian randomized controlled trials (RCTs) from PubMed and Cochrane Libraries to inform a network meta-analysis (NMA). We considered the ARB-AML CT. The primary efficacy and safety endpoints were short-term (8–12 weeks) treatment response and treatment-emergent adverse events (TEAEs), respectively. AML monotherapy was used as a comparator to allow for indirect treatment effect estimation in the absence of direct RCTs evidence comparing the different ARB-AML CTs. Results. The analysis included 1198 Asian HTN patients from seven studies involving six ARB-AML CTs: azilsartan (AZL), candesartan (CAN), fimasartan (FIM), losartan (LOS), olmesartan (OLM), and telmisartan (TEL). Compared to AML monotherapy, CT of AZL-AML had five times greater odds of prompting a treatment response (OR 5.2, 95% CI: 2.5, 11.2), while CAN-AML had 3.9 (95% CI: 2.5, 6.4), FIM-AML had 3.4 (95% CI: 1.4, 8.5), TEL-AML had 3.3 (95% CI: 1.6, 7.1), OLM-AML had 2.7 (95% CI: 1.6, 5.0), and LOS-AML had 2.0 (95% CI: 0.6, 7.3). All ARB-AML CTs had safety profiles comparable to AML monotherapy except TEL-AML, which had significantly lower odds of TEAEs (0.26 (95% CI: 0.087, 0.70)). Conclusion. This study suggests that all ARB-AML CTs compared favorably to AML monotherapy regarding short-term treatment response in uncomplicated HTN patients of Asian origin. AZL-AML prompted the most favorable treatment response. Safety profiles among the ARB-AML CTs were largely comparable. Due to the limited study size and small number of trials (direct evidence), our findings should best be interpreted as an exploratory effort importance to inform future research direction.